Reformulasi Sistem Perencanaan Pembangunan Nasional Dengan Konsep Garis Besar Haluan Negara - Zhafran, Dhafin; Syahuri, Taufiqurrohman; Hadi, Syamsul (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
National development planning is essential for realising sustainable and inclusive development goals. However, the current planning system faces various challenges. This research aims to create a more consistent development framework by revitalising the Outline of State Policy concept. The research method used is normative juridical with statutory, historical, and comparative approaches. This article highlights the lack of effectiveness of the National Development Planning System that replaced the role of the State Policy Guidelines in ensuring long-term development sustainability, including policy inconsistencies across governments in Indonesia. Therefore, reformulation using the Garis Besar Haluan Negara concept is considered urgent. This research finds two options for reform limited amendment of Article 3 Paragraph (1) of the 1945 Constitution or strengthening regulations through revision of Law No. 25/2004 on the National Development Planning System.